GAMIFYING SOCIAL CHANGE: DESIGNING A MOBILE GAME TO PROMOTE PRO-ENVIRONMENTAL BEHAVIORS AS A SOCIAL ENTREPRENEURSHIP INITIATIVE - Lucas Wong; Seo Jiwon; Ingrid Olsson; Dodi Setiawan Riatmaja (Journal of Social Entrepreneurship and Creative Technology, 2025)
The environmental “attitude-action gap” persists, as most “green apps” fail to motivate users or achieve long-term financial sustainability. This study aims to design, develop, and test a mobile game framework that bridges this gap by integrating behavioral psychology with a sustainable social entrepreneurship model. Design-Based Research (DBR) approach was used, culminating in a 6-week, mixed-methods pilot study (n=500). Data was collected via in-game analytics, pre/post-test surveys (Pro-Environmental Behavior Scale, PEBS; Intrinsic Motivation Inventory, IMI), and qualitative interviews. The intervention yielded strong engagement (28.1% Wk6 retention) and a statistically significant increase in self-reported Pro-Environmental Behaviors (PEBS) (p < .001, Cohen’s d = 0.82). High intrinsic motivation (4.4/5.0 IMI) was observed, with ‘Social Relatedness’ (? = .45) being the strongest predictor of retention. The B2C social enterprise model was validated., when co-designed as a social enterprise, is empirically validated as an effective and sustainable framework for motivating PEBs. The model successfully bridges the attitude-action gap by prioritizing social connection.